Exploring provincial eco-efficiency and its coupling relationship with natural gas consumption in China. (January 2022) - Hu, Dongou; Qin, Manman; Sun, Renjin; Dong, Kangyin
Highlights: Measured the provincial eco-efficiency (EE) with undesirable outputs. Estimate the interaction of natural gas consumption (NGC) and EE. Regional disparity and spatial agglomeration characteristics exist simultaneously. Increased investment in technology can narrow the regional gap in EE. The coupling degree of EE and NGC shows an upward trend. Abstract: With rapid economic development and massive greenhouse gas emission, eco-efficiency (EE) has gained significant attention. Natural gas is a crucial clean energy, and has significant influence on EE. Based on the panel data of 30 provinces in China from 2000 to 2017, this research studied the potential improvements in environmental regulation, industrial structure, capital investment, and technological investment of ineffective provinces. In addition, the coupling relationships between natural gas consumption (NGC) and EE are researched, and examined the parameters marginal effect by using quantile regression. The results indicate that, first, there are large inter-provincial differences in the improvement potential. Investment in technology is effective in China's current development stage, and its improvement can largely promote EE. Second, the dynamic evolution relationship between NGC and EE among provinces has no same patterns. Finally, the coupling degree of EE and NGC shows an upward trend, and the provincial average coupling degree increased by 62.6% from 0.564 in 2000 to 0.917 in 2017, indicates a harmonious coordinate relationship trend between the EE and NGC level. As a result, a series of measures are put forward to better promote the development of provincial NGC and EE.